Pelatihan Media Scrapbook dalam Meningkatkan Kreatifitas Guru di Desa Balongsari - Hidayatur Rohmah; Agustina, Ulfa Wulan; Khotimah, Khusnul; Rohmah, Fiki Nailatur; Risianti, Juwita; Asshohib, M. Kholfan Hakim; Syafiudin, Mohammad Afif (Jumat Pertanian: Jurnal Pengabdian Masyarakat, 2024)
The purpose of this service is to provide interesting material treats for students. Because with this, the teacher can convey an overview of the material being taught visibly, so that students can understand the material concretely and create a more effective and interactive learning environment. scrapbook learning at SDN Balongsari which is the target of community service activities. The method of approach to community service in Balongsari village is Participatory Action Research (PAR) which aims to learn in dealing with problems and meeting the practical needs of partners, as well as generating knowledge and encouraging social change in the religious realm. The results of the service show that the socialization and media making activities increase the creativity of educators at SDN Balongsari as a means or learning media. Socialization activities and making scrapbook learning media are very useful for increasing students' interest in learning so that they are not bored when learning in class. Socialization and making scrapbook learning media involving teachers so that teachers understand learning media that attracts learning interest for their students. The products produced in the socialization and making of this learning media are in the form of creative books or scrapbooks which contain some material about prayer procedures arranged in such a way with interesting decorations and trinkets.